2004
DOI: 10.1002/anie.200352468
|View full text |Cite
|
Sign up to set email alerts
|

Gd5Si2B8: A Ternary Rare‐Earth‐Metal Silicide Boride Compound

Abstract: In spite of the extensive experimental attention devoted to the various structural and physical properties of binary borides [1] and silicides [2] of the rare-earth metals (RE), there are comparatively few investigations of ternary silicide borides. Indeed, only a few boron-rich rare-earth metal silicide borides such as RESiB 44 , RESi 4.6 B 17.6 , RESi 1.2 B 41 (RE = Gd!Er, Y), [3] and Tb 3Àx C 2 Si 8 B 36[4] containing icosahedral B 12 cages, are known. This situation is in contrast with the ternary boride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The line compound RE 5 Si 2 B 8 of Gd 5 Si 2 B 8 -type structure exhibits an intergrown structure, which is formed by the stacking of ThB 4 -and U 3 Si 2 -type slabs alternating along the c axis of the tetragonal lattice [3,20]. The crystal structures of all the RE 5 Si 2 B 8 phases (RE = Dy, Ho and Y) were recently reported [21].…”
Section: Isothermal Section Of the Ternary Phase Diagramsmentioning
confidence: 96%
“…The line compound RE 5 Si 2 B 8 of Gd 5 Si 2 B 8 -type structure exhibits an intergrown structure, which is formed by the stacking of ThB 4 -and U 3 Si 2 -type slabs alternating along the c axis of the tetragonal lattice [3,20]. The crystal structures of all the RE 5 Si 2 B 8 phases (RE = Dy, Ho and Y) were recently reported [21].…”
Section: Isothermal Section Of the Ternary Phase Diagramsmentioning
confidence: 96%
“…This is supported by the DOS computed at the LMTO DFT level. The Fermi level cuts a rather high peak of DOS, showing that the compound should be metallic in character [42]. The different projected DOS indicate participation of all constituting elements, Gd, B 6 , B 2 , and Si 2 , all over the DOS.…”
Section: Article In Pressmentioning
confidence: 97%
“…Recent works have shown that substituting silicon for carbon leads to compounds with strongly different structural arrangements [41,42]. Several years ago when we thought about extending the RE-B-C chemistry to that of RE-B-Si, a look at the literature on ternary RE-B-Si compounds showed very few results [43].…”
Section: Rare-earth Metal Boron Silicidesmentioning
confidence: 99%
“…The boron and silicon subnets are independent of each other in such a way that no boron-silicon bond occurs in the structure, contrary to the numerous and strong Si-Si and B-B covalent bonds. A more detailed description of the structural type Gd 5 Si 2 B 8 (and isostructural R 5 Si 2 B 8 compounds with R=Sm and Tb) together with theoretical calculations is proposed elsewhere [43]. The ternary phase Gd 5 Si 3 B 0.64 has been obtained from boron-poor samples.…”
Section: Crystal Structuresmentioning
confidence: 99%